2014
DOI: 10.1177/1538192714527314
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Factors Contributing to Successful Completion of Undergraduate Degrees by the Students Enrolled in the College Assistance Migrant Program

Abstract: Students from farmworker families are often cited as having deficits that prohibit completion of undergraduate degree program. Statistics regarding graduates of the College Assistance Migrant Program in a southwestern university have shown graduation rates that are similar to the general population of graduates at that university. This qualitative pilot study reveals some possible implications for how alleged deficits for completing college can be converted into assets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…For instance, Yosso, Smith, Ceja, and Solórzano (2009) found that Latina/o students at three different college campuses reported being subjected to a variety of racial micro-aggressions that left them "feeling like 'outsiders' within their own universities" (p. 680). These researchers also found-as other research has shown (i.e., Gonzalez et al, 2004;Zalaquett, 2005;Escamilla & Trevino, 2014;Ojeda, Castillo, Meza, & Pina-Watson, 2014;Rodriguez & Oseguera, 2015;Gonzales, Brammer, & Sawilowsky, 2015)-that Latina/o students respond to such negative racial climates by forming their own campus communities wherein their cultural wealth and ethnic identities are aligned with their "home communities." Such ethnic and cultural enclaves on campuses have been shown to enhance retention of Latina/o students.…”
Section: College Environments Antagonistic To Diversitymentioning
confidence: 53%
See 4 more Smart Citations
“…For instance, Yosso, Smith, Ceja, and Solórzano (2009) found that Latina/o students at three different college campuses reported being subjected to a variety of racial micro-aggressions that left them "feeling like 'outsiders' within their own universities" (p. 680). These researchers also found-as other research has shown (i.e., Gonzalez et al, 2004;Zalaquett, 2005;Escamilla & Trevino, 2014;Ojeda, Castillo, Meza, & Pina-Watson, 2014;Rodriguez & Oseguera, 2015;Gonzales, Brammer, & Sawilowsky, 2015)-that Latina/o students respond to such negative racial climates by forming their own campus communities wherein their cultural wealth and ethnic identities are aligned with their "home communities." Such ethnic and cultural enclaves on campuses have been shown to enhance retention of Latina/o students.…”
Section: College Environments Antagonistic To Diversitymentioning
confidence: 53%
“…While these gender roles are reflective of those within a larger societal context, the gender roles Latina adolescents from traditional families are often expected to fulfill promote that they not engage activities that may deliver them from the domestic realm. However, Escamilla and Trevino (2014) found that these cultural bindings which can place stress upon Latinas in particular can be destabilized once their families take an active role in the college going process. Alvarez (2010), for instance, has shown that when Latina/o parents and their daughters all participate in the process of selecting a college and navigating the path toward college enrollment, Latina students have smoother transitions from home to college.…”
Section: Hispanic Cultural Norms That Promote Family Interdependence mentioning
confidence: 99%
See 3 more Smart Citations